Cannabidiol Mitigates Deoxynivalenol-Induced Intestinal Toxicity by Regulating Inflammation, Oxidative Stress, and Barrier Integrity - Lingchen Yang; Tristan Decas; Yuhang Zhang; Imourana Alassane-Kpembi (Toxins)
The deoxynivalenol (DON) mycotoxin poses serious health risks, especially to swine, which are highly susceptible to intestinal damage. Existing strategies to counteract DON toxicity remain insufficient. This study aimed to evaluate the protective effects of cannabidiol (CBD), a phytocannabinoid with anti-inflammatory properties, against DON-induced intestinal toxicity in porcine intestinal epithelial cells. Using differentiated and proliferating porcine intestinal epithelial cells (IPEC-J2), we evaluated CBD (2.5–5 μM) against DON (0.5–50 μM) through viability assays, apoptosis markers (Bax/Bcl-2 ratio), inflammatory mediators (NFκB, IL-6, COX-2), oxidative stress indicators (TXNIP, SOD1, CAT), tight junction gene expression (Claudin-1, Occludin), and barrier permeability. DON exhibited dose- and time-dependent cytotoxicity (IC50 = 2.60 μM at 24 h; 1.07 μM at 48 h). Pre-treatment with 5 μM CBD restored cell viability at low DON concentrations (0.5–2 μM) but failed at ≥8 μM. In differentiated cells, CBD suppressed apoptosis (reduced Bax/Bcl-2 ratio), oxidative stress (downregulated TXNIP; restored CAT expression), and inflammation (decreased IL-6 and COX-2) under high-dose DON (50 μM), while enhancing tight junction protein expression and barrier integrity at 5 μM DON. Conversely, in proliferating cells, CBD exacerbated apoptosis (elevated Bax/Bcl-2 ratio) and inflammatory responses (upregulated IL-6 and COX-2) at subtoxic levels of DON (2 μM). CBD alone induced cytotoxicity at ≥10 μM. Our findings demonstrate that CBD exhibits context-dependent efficacy, providing protection in differentiated epithelia under moderate DON exposure (≤5 μM) but exhibiting detrimental effects in proliferating cells. Its narrow therapeutic window and paradoxical actions necessitate cautious application. These findings position CBD as a potential adjunctive therapy for DON detoxification but highlight critical limitations for standalone use.